Improvement of the methodology for predicting gas-dynamic phenomena on the basis of modern sound-capturing equipment - Krasnyk, Vyacheslav; Deglin, Boris (Technology audit and production reserves, 2024)
The object of the study is the sound accompaniment of the processes of stress redistribution in the bottom part of the coal seam, which precede the release of rock, coal, and gas. Among the hazards of underground coal mining, gas-dynamic phenomena (GDP) are the most complex in nature and the most dangerous in terms of consequences of high dynamic power and the release of a large amount of mechanical energy in the form of fractures and gas in a short period of time. This leads to accidents due to sudden gassing and blockages of workings with coal and rock, as well as explosions of methane and coal dust, destruction of the workings' support, damage to machinery and mechanisms, equipment, and devices. The greatest hazard among GDPs is posed by sudden releases of coal and gas, rock and gas, gas releases with destruction of host rocks and with destruction of the ground of the workings, as well as gas breakthroughs from tectonic fault zones. Therefore, the accuracy of predicting possible gas-dynamic phenomena significantly affects the level of safety of miners. The acoustic emission (AE) method is used to predict the gas-dynamic activity of a rock massif. The analysis of acoustic emission studies based on archival data in coal seams subject to gas-dynamic activity has made it possible to substantiate the possibility of improving the accuracy of the forecast of emission hazard, which has a social and economic effect. On the basis of exploratory research and production tests, the software for automated calculations of the GDP forecast was improved and an improved Methodology for forecasting gas-dynamic phenomena based on modern sound-capturing equipment was developed. A scientific justification for the reference interval of AE observations in the conditions of a particular longwall was developed. The developed software and the forecasting methodology were tested in the conditions of the Tsentralna mine of the Toretskugol State Enterprise (Toretsk, Donetsk region, Ukraine). The practical significance of the work is that a method for predicting explosion hazard has been developed, taking into account the modern capabilities of equipment and methods of input data processing, which allows to increase the productivity of mining and tunneling operations in coal seams without reducing the safety of miners.